Ferry transportation in Abidjan: Establishment, operation and sustainability of a paratransit system - Estelle Gnankon Kabran; Irit Eguavoen (University of Bonn, Center for Development Research (ZEF), 2019)
Abidjan, the economic capital of Côte d'Ivoire, is built around the Ebrié lagoon on the Atlantic Ocean. Boats and ferries have always been part of the urban transport system. Ferries (pinasses) are essential to enable particularly the poor to maintain their mobility. The objective of this study is to analyse the establishment, operation and sustainability of waterways and quays in Abidjan. The paper presents data on 11 wooden, diesel-driven ferry lines that connect one inner city peninsula, on which the informal and precarious settlement Adjahui is located, with other parts of the metropolis. From 2012 onwards, this paratransit ferry system has been established by private entrepreneurs who recognised the growing demand for water transit as well as its high business potential. Data from geographic information system (GIS) mapping, a survey among customers (n = 384), nine in-depth interviews and counting of customers revealed that - despite operating about 54,500 rides a day - this ferry transport is unpopular among the population. Most, however, have no transport alternative. Passengers usually commute between their homes and workplaces on a daily basis but also keep connections to their former quarters of residence. Though pinasses provide a demand-driven, effective and rather sustainable transit system, further investments are needed to improve services and security, as well as the quality of the quays and provide more environment-friendly machinery. Current profits of private entrepreneurs would allow these investments, but findings indicate that insecurity with regard to retention periods, as well as investments as a short-term strategy rather discourage further private investments.
Keywords: 330; informality; urban transport; Abidjan; paratransit; water transit; private sector; Africa